Pembrolizumab alone or with chemotherapy for 70+ year-old lung cancer patients: a retrospective study - Blasi, Miriam; Kuon, Jonas; Shah, Rajiv; Bozorgmehr, Farastuk; Eichhorn, Florian; Liersch, Stephan; Stenzinger, Albrecht; Heußel, Claus Peter; Herth, Felix; Thomas, Michael; Christopoulos, Petros (Clinical lung cancer, 2023)
Objective - First-line pembrolizumab alone, as approved for PD-L1 ≥50%, or with chemotherapy was analyzed in older non-small-cell lung cancer (NSCLC) patients, for whom evidence is scarce. - Materials and Methods - A total of 156 consecutive ≥70 year-old patients treated between January 2016 and May 2021 were retrospectively analyzed. Tumor progression was verified through radiologic review, while toxicity was captured from records. - Results - Pembrolizumab plus chemotherapy (n = 95) caused higher rates of adverse events (91% vs. 51%, P < .001), treatment discontinuation (37% vs. 21%, P = .034), and hospitalization (56% vs. 23%, P < .001), but similar rates of immune-related adverse events (irAEs, mean 35%, P = .998) compared to pembrolizumab monotherapy (n = 61). Progression-free (PFS) and overall survival (OS) were similar between the 2 groups (7 vs. 8 months, and 16 vs. 14 months in median, P > .25). Occurrence of irAEs was associated with longer survival in a 12-week landmark analysis (median PFS 11 vs. 5 months, hazard ratio [HR] 0.51, P = .001; median OS 33 vs. 10 months, HR 0.46, P < .001), but occurrence of other AEs not (both P > .35). A worse ECOG performance status (PS) ≥2, presence of brain metastases at diagnosis, squamous histology and lack of tumor PD-L1 expression were independent predictors of shorter PFS and OS in multivariable analysis (HR 1.6-3.9 for PFS and OS, all P < .05). - Conclusion - Chemoimmunotherapy increases the rate of adverse events and hospitalization without prolonging PFS or OS in newly diagnosed NSCLC patients aged 70 years or older compared to pembrolizumab monotherapy. ECOG PS 2, presence of brain metastases at diagnosis, squamous histology and PD-L1 negativity are associated with poor outcome.